냉간압연률 및 두께에 따른 STS316L의 감쇠능 및 고유주파수 - 남기우(Ki-Woo Nam); 김병수(Byeong-Su Kim); 김진욱(Jin-Wook Kim); 손대진(Dai-Jin Son); 최병철(Byoung-Chul Choi) (동력시스템공학회지, 2020)
본 연구는 오스테나이트 상 STS316L강을 사용하여, 진동 및 지진 등에 의한 탄성파를 흡수 또는 감쇠 가능성을 연구하였다. 오스테나이트 상 STS316L강은 냉간압연률을 다르게 하고, 마르텐사이트 상으로 변태시켰다. 이것을 사용하여 기계적 특성 및 감쇠능을 조사하였다. 또한, 냉간압연재는 고유주파수를 구하였으며, 두께가 다른 모재의 고유주파수와 비교하였다. 인장강도는 냉간압연률의 증가에 따라서 ε-마르텐사이트로 많이 변태하여, 증가하였으나, 연신율은 급격하게 감소하였다. 감성은 냉간압연률이 많을수록 증가하여, 감쇠능은 좋아졌다. 고유주파수는 냉간압연률이 많아짐에 따라서 약간 감소하는 경향을 나타내었으나, 두께가 증가함에 따라서 증가하는 경향을 나타내었다. FFT분석한 고유주파수는 2차 주파수로 나타났다. 고유주파수 비는 일정한 값을 나타내고, 조직의 영향은 없었다. This study was investigated mechanical properties, damping capacity and natural frequency using STS316L steel with different thickness and cold rolled STS316L steel. The austenite phase was transformed into a martensite phase by cold rolling. Tensile strength increased with an increase of the degree of cold rolling whereas elongation decreased. The damping capacity decreased as the degree of cold rolling increased. The natural frequency showed a tendency to decrease slightly as the degree of cold rolling increased, and increased as the thickness increased. The natural frequency of the FFT analysis was found to be the secondary frequency. The natural frequency ratios showed a constant value, and there was no structure effect. KCI Citation Count: 1